Expanding Maternal and Neonatal Survival in Indonesia: A program overview. (27th February 2019) - Hyre, Anne; Caiola, Nancy; Amelia, Dwirani; Gandawidjaja, Trisnawaty; Markus, Sudibyo; Baharuddin, Mohammad
Abstract: The Expanding Maternal and Neonatal Survival (EMAS) program was implemented from September 2011 to March 2017 to support the Indonesian Ministry of Health to improve the quality of emergency obstetric and newborn care, increase the efficiency and effectiveness of emergency referrals, and increase accountability through local government and civic engagement. EMAS worked in over 400 public and private referral hospitals and community health centers ( puskesmas ) in six provinces where over 50% of all maternal deaths were occurring. Mentoring was the main method used to improve performance at facilities and within referral systems. The use of data for prospective assessment of indicators of improved quality of care and referral efficiency was strengthened. Case reviews were used to examine contextual factors contributing to maternal deaths in EMAS‐target hospitals and external evaluations were used in retrospective assessments of effectiveness of approaches. The vision of sustainability was infused into EMAS approaches from the outset. Collaboration and advocacy with district health offices in EMAS‐supported districts enabled self‐funding of selected interventions within 23 of 30 EMAS districts and 35 non‐EMAS districts. Articles in this Supplement describe outcomes and impact of EMAS approaches over the term of the program. Abstract : The EMAS program impacted quality of emergency obstetric and neonatal care, efficiency and effectiveness of referrals, and increased accountability through mentoring in six Indonesian provinces.